Risk factor Analysis and Angiographic Profiles in First 228 Cases Undergone Coronary Angiography in Cardiac Cath Lab of Dhaka Medical College Hospital - Islam, AEMM; Faruque, M; Chowdhury, AW; Khan, HIR; Haque, MS; Ali, MS; Khan, M; Sharma, PK; Anar, F; Karim, MA; et al. (Cardiovascular Journal, 2011)
Background: Coronary artery diseases are one of the major challenges faced by cardiologists. Control of certain risk factors for CAD is associated with decrease in mortality and morbidity from myocardial infarction and unstable angina. So, identification and taking appropriate measures for primary and secondary prevention of such risk factors is, therefore, of great importance. This retrospective study was carried at the newly set up cath lab in Dhaka Medical college. Materials and Methods: Total 228 consecutive case undergone diagnostic coronary angiogram from 10th January 2007 to31st January 2009 out of which 194(80%) were male and 34 (20%) were female. In both sexes most of the patients were between 41 to 60 years of age. Risk factors of the patients were evaluated. Results: In females commonest risk factor was Diabetes (58.8%) followed by dyslipidaemia (35.3%). In males commonest risk factor was hypertension (30.9%) followed by smoking (29.9%) and diabetes (28.3%). In males 44.3% patients presented with acute myocardial infarction followed by stable angina (43.3%); but in females stable angina was the commonest presentation (50.0%) followed by myocardial infarction (38.2%).CAG findings revealed that in males 33.5% had double vessel disease 26.8% followed by single vessel 26.8% and multivessel disease 25.3%. In females normal CAG was found in 35.5% followed by double vessel 23.5%, multivessel 20.6% and single vessel 20.6%. On the basis of CAG findings; in males 41.8% patients were recommended for CABG, followed by PTCA & stenting 26.3% and medical therapy 30.0%; where as in females 55.9% were recommended for medical therapy , followed by CABG 32.4% and PTCA & stenting11.8%. Conclusion: The commonest presentation of CAD was 4th and 5th decades in both sexes. Diabetes and dyslipidaemia were more common in females whereas hypertension and smoking were more common in males. Myocardial infarction and stable angina were most common presentation in both sexes though in males myocardial infarction was more common. In males the angiographic severity of CAD was more and they were more subjected for CABG in comparison to females. Key words: Risk factors; Coronary angiography. DOI: http://dx.doi.org/10.3329/cardio.v3i2.9179 Cardiovasc. J. 2011; 3(2): 122-125